Determinasi Non-Performing Loans Pada Perbankan ASEAN-10: Analisis Pengaruh Variabel Makroekonomi - audia sandy (Economie: Jurnal Ilmu Ekonomi, 2026)
Banking sector stability plays an important role in maintaining the resilience of a country’s financial system. One of the key indicators reflecting bank asset quality is the Non-Performing Loans (NPL) ratio. A high level of NPL may increase credit risk and potentially threaten financial stability. This study aims to examine the effect of macroeconomic factors, namely Gross Domestic Product (GDP), inflation, and unemployment, on Non-Performing Loans in the banking sector across ASEAN countries. The study employs a quantitative approach using secondary data obtained from the World Bank covering the period 2014–2023. The analysis method applied is dynamic panel data estiomation using the Generalized Method of Moments to address potential endogeneity and capture dynamic effects in the model. The results indicate that Gross Domestic Product has a negative and significant effect on Non-Performing Loans, suggesting that higher economic growth can reduce the level of non-performing loans in the banking sector. Meanwhile, inflation and unemployment do not have a significant impact on Non-Performing Loans. These findings highlight the importance of maintaining economic stability and sustainable growth to support banking sector performance and minimize credit risk.